A degradable coating composite fabric prepared using biological residues and preparation method thereof

Through the combination technology of water-based polyurethane emulsion and water-based RPVB emulsion, combined with bio-based fillers and additives, the problem of poor compatibility between bio-based fillers and matrix resins is solved, and the good mechanical properties and environmental protection performance of composite fabrics are achieved, which is in line with the development trend of low-carbon and environmental protection.

CN116219764BActive Publication Date: 2025-03-25HANGZHOU RECOTEC SOLUTIONS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310034299.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-10
Publication Date
2025-03-25
Estimated Expiration
2043-01-10

AI Technical Summary

Technical Problem

In the prior art, bio-based fillers have poor compatibility with matrix resins, resulting in a deviation in mechanical strength of composite fabrics, and there is a lack of composite surface materials that meet biodegradable and expected physical and chemical properties on the market.

Method used

The composite emulsion formed by combining aqueous polyurethane emulsion and aqueous RPVB emulsion as the matrix, combined with bio-based fillers such as pineapple residue powder, coconut shell powder, etc., the mechanical and environmental performance of the composite fabric is improved by modifying bio-based fillers and adding compatibility agents and anti-ultraviolet additives.

Benefits of technology

The better mechanical properties and green environmental protection properties of composite fabrics have been achieved, the mechanical strength deviation problem in the existing technology has been overcome, and it is in line with the development trend of low-carbon environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004048638260000131
    Figure BDA0004048638260000131
  • Figure BDA0004048638260000141
    Figure BDA0004048638260000141
Patent Text Reader

Abstract

The present application relates to the technical field of preparation of degradable fabrics, in particular to a degradable coating composite fabric prepared using biological residues and a preparation method thereof. A degradable coating composite fabric prepared using biological residues includes a base fabric, and a degradable coating is compounded on the surface of the base fabric; the degradable coating is mainly made of the following raw materials in parts by weight: aqueous RPVB emulsion, aqueous polyurethane emulsion, compatibilizer, anti-ultraviolet additive, antioxidant, dispersant, bio-based filler; the bio-based filler is one or more combinations of pineapple residue micropowder, coconut shell micropowder, coffee grounds micropowder, carbonized pineapple residue micropowder, carbonized coconut shell micropowder, carbonized coffee grounds micropowder, pineapple residue-based activated carbon, coconut shell-based activated carbon, and coffee grounds-based activated carbon. The present application not only has good degradability and good environmental performance, and is in line with the development trend of low-carbon and environmental protection, but also has relatively good physical properties, which can improve the overall mechanical properties of the fabric and expand its scope of application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of preparation of degradable fabrics, and in particular to a degradable coating composite fabric prepared by using biological residues and a preparation method thereof. Background Art

[0002] As the contradiction between resources and the environment becomes increasingly intensified, plastic degradable recycling technology has become a hot subject. The application of plastic degradable recycling technology in the field of composite fabrics, such as the use of biodegradable fibers to produce fabrics that can be degraded by heating. Common degradable fibers include polylactic acid fibers, protein fibers, soybean fibers, and the like. At present, the plastic degradable recycling technology in base fabrics has basically matured, but as a composite surface material for base fabrics, a composite surface material that is biodegradable and meets the expected physical and chemical properties has not appeared in the current market. Therefore, the present application provides a degradable coating composite fabric prepared using biological residues and a preparation method thereof. Summary of the invention

[0003] In order to solve the above technical problems, the present application provides a degradable coated composite fabric prepared using biological residues and a preparation method thereof.

[0004] In the first aspect, the present application provides a degradable coating composite fabric prepared using biological residues, which is achieved through the following technical solutions:

[0005] A degradable coating composite fabric prepared by using biological residues, comprising a base fabric, wherein the base fabric surface is composited with a degradable coating; the degradable coating is mainly prepared from the following raw materials in parts by weight: 80-100 parts of water-based RPVB emulsion, 20-25 parts of water-based polyurethane emulsion, 3-8 parts of a compatibilizer, 0.5-2 parts of an anti-ultraviolet additive, 0.5-2 parts of an antioxidant, 1-5 parts of a dispersant, and 12-45 parts of a bio-based filler; the water-based RP The solid content of the VB emulsion is 40-55%, and the solid content of the aqueous polyurethane emulsion is 30-45%; the average particle size of the bio-based filler is controlled to be 0.1-10 μm; the bio-based filler is one or a combination of pineapple residue powder, coconut shell powder, coconut shell fiber, coffee grounds powder, carbonized pineapple residue powder, carbonized coconut shell powder, carbonized coconut shell fiber, carbonized coffee grounds powder, pineapple residue-based activated carbon, coconut shell-based activated carbon, and coffee grounds-based activated carbon.

[0006] In this application, a composite emulsion formed by compounding an aqueous polyurethane emulsion and an aqueous RPVB emulsion is used as a matrix, which overcomes the defect of mechanical strength deviation caused by poor compatibility between bio-based fillers and matrix resins in the prior art, and gives the degradable coating composite fabric better mechanical properties and better green environmental protection performance. This application not only has good degradability and good environmental protection performance, which conforms to the development trend of low-carbon and environmental protection, but also has relatively good physical properties, which can improve the overall mechanical properties of the fabric and expand its application range.

[0007] Preferably, the degradable coating is mainly prepared from the following raw materials in parts by weight: 100 parts of aqueous RPVB emulsion, 20-25 parts of aqueous polyurethane emulsion, 4-6 parts of compatibilizer, 0.8-1.2 parts of anti-UV additive, 1-1.5 parts of antioxidant, 3-4 parts of dispersant, 25-35 parts of bio-based filler, 0.5-2 parts of aqueous crosslinker, 0.5-2 parts of mineral oil-based defoamer, 1-3 parts of hydrophilic antifouling agent; the aqueous crosslinker is one of Neoadd PAX-524 aqueous crosslinker and Crosslinker CX-100 aqueous crosslinker; the mineral oil-based defoamer is one of Foamaster MO 2150 and Foamaster MO NXZ; the hydrophilic antifouling agent is one of KP-912, KP-913 and KP-914.

[0008] By adopting the above technical solution, the processing performance of the present application is improved, the production of degradable coated composite fabrics is facilitated, and at the same time the quality and quality stability of the same batch of degradable coated composite fabrics are improved.

[0009] Preferably, the bio-based filler is carbonized coconut shell fiber filaments, carbonized coffee grounds powder, and coffee grounds-based activated carbon; the length of the carbonized coconut shell fiber filaments is 3-10 μm; the carbonized coffee grounds powder is composed of nano-carbonized coffee grounds powder with a particle size distribution of 0.1-0.3 μm and submicron carbonized coffee grounds powder with a particle size distribution of 1-3 μm; the mass ratio of the nano-carbonized coffee grounds powder with a particle size distribution of 0.1-0.3 μm and the submicron carbonized coffee grounds powder with a particle size distribution of 1-3 μm is (6-8): (2-4); the average particle size of the coffee grounds-based activated carbon is controlled at 3-6 μm.

[0010] By adopting the above technical solution, the compatibility of the bio-based filler and the matrix emulsion can be improved, thereby enhancing the mechanical strength of the degradable coating composite fabric prepared in the present application.

[0011] Preferably, the mass of the carbonized coconut shell fiber filaments accounts for 10-30wt% of the total mass of the bio-based filler, the mass of the carbonized coffee grounds powder accounts for 20-50wt% of the total mass of the bio-based filler, and the remainder is coffee grounds-based activated carbon.

[0012] By adopting the above technical solution, the compatibility of the bio-based filler and the matrix emulsion can be further improved, thereby enhancing the mechanical strength of the degradable coating composite fabric prepared in the present application.

[0013] Preferably, the aqueous polyurethane emulsion is made from the following raw materials: isocyanate, polyol, catalyst, chain extender, dimethylglyoxime, triethanolamine, acetone, and deionized water; the chain extender is 1,6-hexanediol and ethylenediamine; the molar ratio of 1,6-hexanediol to ethylenediamine is 1:(0.5-2); the polyol is polycarbonate polyol and polytetrahydrofuran polyol with a weight average molecular weight of 2000-3000; the molar ratio of the polycarbonate polyol to polytetrahydrofuran polyol is (8-9):(1-2); the molar ratio of the active groups in the dimethylglyoxime is 0.2-0.4 times the total molar amount of the active groups in the polyol and the chain extender; the molar ratio of the polyol to the chain extender is 1:(2.5-2.8).

[0014] By adopting the above technical solution, the prepared waterborne polyurethane emulsion has relatively good compatibility with the bio-based filler, thereby ensuring the overall mechanical properties, wear resistance and environmental performance. And diacetyl oxime, as a self-healing active matrix, can improve the puncture resistance of the formed degradable coating and is also conducive to environmental degradation.

[0015] Preferably, the preparation method of the aqueous polyurethane emulsion comprises the following steps: firstly weighing the polyol, isocyanate and catalyst according to the formula, mixing them evenly, heating to 85-95°C, reacting for 2-2.5h, adding the chain extender, reacting at 70-80°C for 40min, adding dimethylglyoxime, and continuing to react for 1-1.5h; then adding acetone to dilute, cooling to 40-45°C, adding triethanolamine to neutralize, adding deionized water to disperse evenly at high speed, and distilling to remove acetone to obtain the target aqueous polyurethane emulsion.

[0016] The preparation method of the present application is relatively simple and is convenient for mass production and processing.

[0017] Preferably, the dispersant is a composite coupling agent and one of Dispex Ultra FA 4416, 4420, and 4430; the preparation method of the composite coupling agent is to mix N-phenylaminomethyltriethoxysilane and 3-methacryloxypropyltriethoxysilane in a molar ratio of 1: (1.02-1.08) evenly, and reflux the mixture at 80-95° C. for 3-6 hours to obtain the composite coupling agent.

[0018] By adopting the above technical solution, the bio-based filler is evenly distributed in the matrix emulsion, and the compatibility of the bio-based filler and the matrix emulsion is improved, thereby ensuring the mechanical properties and environmental protection performance of the present application.

[0019] Preferably, the dispersant is a composite coupling agent with Dispex Ultra FA 4420 and a titanate crosslinker TA-9-2; the mass ratio of the composite coupling agent, Dispex Ultra FA 4420, and the titanate crosslinker TA-9-2 is (6-8): 1:1.

[0020] By adopting the above technical solution, the bio-based filler is evenly distributed in the matrix emulsion, the compatibility of the bio-based filler and the matrix emulsion is further improved, and the overall mechanical properties and environmental performance of the present application are guaranteed.

[0021] Preferably, the antioxidant is one or more combinations of antioxidant 1010, antioxidant 168, antioxidant 1076, and antioxidant 1024; the anti-UV auxiliary agent is one or more combinations of UV-326, UV-292, UV-77DF, Tinuvin 1130, Tinuvin 5151, and Tinuvin 5333-DW (N); and the compatibilizer is one or more combinations of POP grafted maleic anhydride, TPO, TPV, TPU, and TPEE.

[0022] By adopting the above technical solution, the antioxidant and anti-ultraviolet additive are used in combination to give the present application good weather resistance. The addition of a compatibilizer can improve the compatibility of the bio-based filler and the matrix emulsion, ensuring the overall mechanical properties and environmental performance of the present application.

[0023] In the second aspect, the present application provides a method for preparing a degradable coating composite fabric prepared using biological residues, which is achieved through the following technical solutions:

[0024] A method for preparing a degradable coating composite fabric prepared by using biological residues, comprising the following steps:

[0025] Step 1, preparing an aqueous polyurethane emulsion; at the same time, evenly mixing the bio-based filler and the dispersant to obtain a modified bio-based filler; Step 2, evenly mixing the accurately measured aqueous polyurethane emulsion and the aqueous RPVB emulsion, adding the modified bio-based filler, and stirring at 200-300 rpm for 10-20 minutes;

[0026] Step 3, add compatibilizer, anti-ultraviolet additive, antioxidant, stir at 200-300rpm for 20-30min, and vacuum defoam to obtain the finished degradable coating;

[0027] Step 4, the base fabric is washed with deionized water and then dried, and the dried base fabric is subjected to plasma treatment to obtain a pretreated base fabric;

[0028] Step 5: Scrape the degradable coating prepared in step 3 onto the surface of the base fabric pretreated in step 4, with the scraping amount controlled at 20-40 g / m 2 After the coating is completed, it is placed at 60-80℃ for drying to form a film to obtain the finished product.

[0029] The preparation method of the present application is relatively simple, convenient for mass production and processing, reduces the use cost, and is convenient for marketing. The composite fabric prepared by the preparation method of the present application has good degradability and good environmental performance, which conforms to the new trend of low-carbon and environmental protection.

[0030] In summary, this application has the following advantages:

[0031] 1. This application has good biodegradability and good environmental performance, which conforms to the new trend of low-carbon and environmental protection.

[0032] 2. The preparation method of the present application is relatively simple and convenient for mass production and processing.

[0033] 3. The production cost of this application is relatively low, which facilitates the recycling of discarded bio-based fillers, rationally utilizes social resources, has good environmental performance, and conforms to the new trend of low-carbon and environmental protection.

[0034] 4. The environmental protection performance of this application is better, and at the same time it overcomes the defects of mechanical strength deviation in the prior art. The degradable coating composite fabric prepared by this application has good mechanical properties and better green environmental protection performance. DETAILED DESCRIPTION

[0035] The present application is further described in detail below in conjunction with comparative examples and embodiments.

[0036] The preparation method of the aqueous RPVB emulsion comprises the following steps:

[0037] Step 1, preparation of RPVB powder:

[0038] S1.1, recycle discarded car windshields, cut off the black part next to the car windshield products, separate the black glass from the transparent glass, so that the transparent glass can be sold at a good price. In addition, the PVB part is also separated into black and white at the same time. The collected PVB products are crushed for the first time and broken into a mesh shape to facilitate soaking and improve cleanliness;

[0039] S1.2, immerse the products broken into nets in S1.1 into the pool, and arrange and stack them neatly to facilitate the subsequent operation. The immersion time is 15 days. The immersion liquid is a 5g / L aqueous solution of fatty acid polyoxyethylene ester non-ionic surfactant. The immersion area needs multiple water channels for immersion to achieve circulation operation;

[0040] S1.3, second crushing: crush the product obtained in S1.2 for the second time to make the product cleanliness reach more than 90%, then flatten it, brush the impurities on the surface of the product, and improve its cleanliness to more than 95%;

[0041] S1.4, dividing the product obtained in S1.3 into noodles to further improve the cleanliness of the product, wherein the cleanliness of the product after treatment is above 98%, and then placing it in a cleaning machine for cleaning to increase the cleanliness of the product to 100%;

[0042] S1.5, granulation, removal of moisture, moisture content is less than 0.01%, and finished RPVB powder is obtained;

[0043] Step 2, add 10 kg of deionized water into the high-speed reactor, start stirring, control the stirring speed at 2000 rpm, add 5 kg of RPVA powder prepared in step 1, 1.0 kg of polyethylene glycol 1000, 20 g of antioxidant 1076 and 5 g of antioxidant 1010 into the high-speed reactor, heat to 90-92 ° C, stir and mix to form an aqueous solution;

[0044] Step 3: After cooling to 29-30°C, add 2.25 kg of butyraldehyde and 0.75 kg of acetaldehyde in sequence, stir for 5 minutes, then continue to cool to 6-8°C, and add 0.86 kg of hydrochloric acid;

[0045] Step 4, then quickly heat up to 35-36°C at a rate of 20°C / h, and maintain between 35-36°C until the system undergoes a transparent-blue milky white transition, and then immediately add about 0.86kg of liquid alkali (sodium hydroxide) to fully neutralize the hydrochloric acid in the system, adjust the pH value of the system to between 6.9-7.1, and then distill under reduced pressure to remove the organic solvent to obtain the product aqueous RPVB emulsion.

[0046] Preparation Example

[0047] Preparation Example 1

[0048] The water-based polyurethane emulsion is mainly prepared from the following raw materials: 125.13 g of isocyanate MDI-50, 192.60 g of caprolactone type polycarbonate polyol with a weight average molecular weight of 2000 (Japan Sairui Co., Ltd.), 48.15 g of polytetrahydrofuran polyol with a weight average molecular weight of 2000, 0.1 g of organic bismuth-bismuth octanoate, 14.8 g of 1,6-hexanediol, 11.29 g of ethylenediamine, 10.06 g of dimethylglyoxime, 150 g of acetone, 690 g of deionized water, and 5 g of antioxidant 1010.

[0049] Preparation method of waterborne polyurethane emulsion: first weigh 192.60g of polycarbonate polyol with a weight average molecular weight of 2000, 48.15g of polytetrahydrofuran polyol with a weight average molecular weight of 2000, 125.13g of isocyanate MDI-50 and 0.1g of bismuth octanoate catalyst according to the formula, mix them evenly, heat to 88-90°C, reflux for 2h, and equip the reactor with an acetone condensation reflux device and a pressure relief device; add 14.8 g of 1,6-hexanediol and 11.29 g of ethylenediamine were added, and the mixture was reacted at 80°C for 40 min. Then, 10.06 g of dimethylglyoxime was added and the reaction was continued for 1.5 h. Then, 150 g of acetone was added for dilution, and the mixture was cooled to 40°C. Triethanolamine was added for neutralization for 5 min. Then, 690 g of deionized water was added for high-speed uniform dispersion. Acetone was removed by distillation. Deionized water was added and the solid content was adjusted to 40% to obtain the target waterborne polyurethane emulsion.

[0050] Preparation Example 2

[0051] The difference between Preparation Example 2 and Preparation Example 1 is that the aqueous polyurethane emulsion is mainly prepared from the following raw materials: 125.13 g of isocyanate MDI-50, 177.78 g of caprolactone type polycarbonate polyol with a weight average molecular weight of 2000 (Japan Sesiri Co., Ltd.), 44.44 g of polytetrahydrofuran polyol with a weight average molecular weight of 2000, 0.1 g of organic bismuth-octanoic acid bismuth, 13.13 g of 1,6-hexanediol, 10.68 g of ethylenediamine, 13.94 g of dimethylglyoxime, 140 g of acetone, 650 g of deionized water, and 5 g of antioxidant 1010.

[0052] Preparation Example 3

[0053] The difference between Preparation Example 3 and Preparation Example 1 is that the aqueous polyurethane emulsion is mainly prepared from the following raw materials: 125.13 g of isocyanate MDI-50, 165.0.8 g of caprolactone type polycarbonate polyol with a weight average molecular weight of 2000 (Japan Sesiri Co., Ltd.), 41.27 g of polytetrahydrofuran polyol with a weight average molecular weight of 2000, 0.1 g of organic bismuth-octanoic acid bismuth, 12.2 g of 1,6-hexanediol, 10.0 g of ethylenediamine, 17.25 g of dimethylglyoxime, 135 g of acetone, 615 g of deionized water, and 5 g of antioxidant 1010.

[0054] Preparation Example 4

[0055] The difference between Preparation Example 4 and Preparation Example 1 is that the aqueous polyurethane emulsion is mainly prepared from the following raw materials: 125.13 g of isocyanate MDI-50, 231.11 g of caprolactone type polycarbonate polyol with a weight average molecular weight of 2000 (Japan Sesiri Co., Ltd.), 57.8 g of polytetrahydrofuran polyol with a weight average molecular weight of 2000, 0.1 g of organic bismuth-octanoic acid bismuth, 17.1 g of 1,6-hexanediol, 13.90 g of ethylenediamine, 180 g of acetone, 800 g of deionized water, and 5 g of antioxidant 1010.

[0056] Example

[0057] Example 1

[0058] A degradable coating composite fabric prepared by using biological residues comprises a base fabric and a degradable coating, wherein the degradable coating is composited on the surface of the base fabric.

[0059] The degradable coating is made of the following raw materials in parts by weight: 80 parts of aqueous RPVB emulsion, 20 parts of aqueous polyurethane emulsion in Preparation Example 1, 4 parts of compatibilizer TPU (Desmopan TPU 60A), 0.8 parts of anti-UV additive-Tinuvin1130, 0.8 parts of antioxidant 1010, 0.2 parts of antioxidant 168, 3 parts of dispersant, 1.2 parts of aqueous crosslinker Crosslinker CX-100, 0.8 parts of mineral oil-based defoamer Foamaster MO 215, 2 parts of hydrophilic antifouling additive KP-912, and 12 parts of bio-based filler.

[0060] The dispersant is a composite coupling agent, Dispex Ultra FA 4420, and a titanate crosslinker TA-9-2. The mass ratio of the composite coupling agent, Dispex Ultra FA 4420, and the titanate crosslinker TA-9-2 is 8:1:1.

[0061] The preparation method of the composite coupling agent comprises the following steps: uniformly mixing N-phenylaminomethyl triethoxysilane and 3-methacryloxypropyl triethoxysilane in a molar ratio of 1:(1.02-1.08), and subjecting the mixture to reflux reaction at 80° C. for 3 hours to obtain the composite coupling agent.

[0062] The bio-based filler is coffee grounds powder, and the preparation method of coffee grounds powder comprises the following steps:

[0063] S1, first rinse the coffee grounds with clean water until the water is colorless;

[0064] S2, then sent to the oven, placed at 80-85°C, and dried until the moisture content is less than 5%;

[0065] S3, placing the coffee grounds in a planetary ball mill for ball milling to obtain coffee grounds powder with a particle size of 0.5-2 microns;

[0066] The coffee grounds powder in S4 and S3 is transferred to a muffle furnace, the temperature is adjusted to 200°C, heat treated for 30 minutes, and then placed in a planetary ball mill for dry ball milling, the ball milling speed is 50 rpm, the ball milling time is 20 minutes, and the finished coffee grounds powder is obtained. The average particle size of the finished coffee grounds powder is between 0.5 and 2 microns.

[0067] A method for preparing a degradable coating composite fabric prepared by using biological residues, comprising the following steps:

[0068] Step 1, preparation of aqueous polyurethane emulsion, see Preparation Example 1;

[0069] At the same time, the preparation of aqueous RPVB emulsion: 20 kg of deionized water was added to the reactor, and 10 kg of PVA, 1.8kg polyethylene glycol 1000, 0.2kg polyethylene glycol 400, 40g antioxidant 1010, 10g antioxidant 168, adjust the temperature to 90°C, stir evenly to form a mixed aqueous solution, then cool to 30-32°C, add 455g butyraldehyde and 1.5kg acetaldehyde in sequence, stir for 30s and then cool to 6-8°C in an ice bath, add 2.0kg hydrochloric acid (concentration 0.5mol / L), then quickly heat to 35°C, react at 35°C until the system undergoes a transparent-blue-milky white transition, immediately add about 2.0kg liquid alkali (NaOH concentration 0.5mol / L), fully neutralize the hydrochloric acid in the system, and obtain an aqueous RPVB emulsion by reduced pressure distillation, and finally add deionized water dropwise to adjust the solid content of the aqueous RPVB emulsion to 48±0.5%, to obtain a finished aqueous RPVB emulsion;

[0070] Meanwhile, in the preparation of coffee grounds micro powder, the coffee grounds raw material is first washed with clean water until the water is colorless, and then sent to an oven, placed at 80-85°C, and dried until the moisture content is less than 5%; the coffee grounds micro powder S3 is placed in a planetary ball mill for ball milling to obtain coffee grounds micro powder with a particle size of 0.5-2 microns. The coffee grounds micro powder is transferred to a muffle furnace, the temperature is adjusted to 200°C, and heat treated for 30 minutes, and then placed in a planetary ball mill for dry ball milling, the ball milling speed is 50rpm, the ball milling time is 20 minutes, and the finished coffee grounds micro powder is obtained. The average particle size of the obtained finished coffee grounds micro powder is between 0.5-2 microns;

[0071] Meanwhile, the preparation of the dispersant is as follows: N-phenylaminomethyl triethoxysilane and 3-methacryloxypropyl triethoxysilane in a molar ratio of 1:1.05 are mixed evenly, and then refluxed at 80°C for 3 hours to obtain a composite coupling agent; 24g of the composite coupling agent is added with 3g of Dispex Ultra FA 4420 and 3g of titanate crosslinking agent TA-9-2, and stirred evenly to obtain a finished dispersant; Step 2: 120g of the prepared coffee grounds micropowder and 30g of the dispersant are mixed evenly in a reactor A to obtain a modified bio-based filler;

[0072] Step 3: Place 200 g of the accurately measured aqueous polyurethane emulsion in Preparation Example 1 and 800 g of the aqueous RPVB emulsion prepared in Step 1 in a reactor B and mix them evenly. Then transfer 120 g of the modified bio-based filler and 3 g of the mineral oil-based defoamer Foamaster MO 2150 in the reactor A to the reactor B, stir at 300 rpm for 15 min, and vacuum for defoaming.

[0073] Step 4: 40 g of compatibilizer TPU is dissolved in 60 g of acetone to obtain a TPU solution. 100 g of TPU solution, 8 g of anti-ultraviolet additive Tinuvin 1130, 8 g of antioxidant 1010 and 2 g of antioxidant 168, 5 g of mineral oil-based defoamer Foamaster MO 2150, 12 g of water-based crosslinker CX-100 and 20 g of hydrophilic antifouling additive KP-912 are added to the reactor B at 300 rpm, and stirred at 300 rpm for 30 min. Vacuum defoaming is performed at the same time to obtain a finished degradable coating;

[0074] Step 5: the base fabric is washed with deionized water, and then placed in an oven and dried at 80° C. until the moisture content is less than 2%. The dried base fabric is subjected to plasma treatment, the treatment gas is oxygen, and the treatment time is 300 seconds, to obtain a pretreated base fabric;

[0075] Step 6: Scrape the degradable coating prepared in step 4 on the surface of the base fabric pretreated in step 4, and control the scraping amount to 32g / m 2 After the coating is completed, it is placed at 70°C for drying to form a film to obtain a finished product that can be degraded and coated composite fabric.

[0076] Example 2

[0077] The difference between Example 2 and Example 1 is that the degradable coating is made of the following raw materials in parts by weight: 80 parts of aqueous RPVB emulsion, 20 parts of aqueous polyurethane emulsion in Preparation Example 2, 4 parts of compatibilizer TPU (Desmopan TPU 60A), 0.8 parts of anti-UV additive-Tinuvin 1130, 0.8 parts of antioxidant 1010, 0.2 parts of antioxidant 168, 3 parts of dispersant, 1.2 parts of aqueous crosslinker Crosslinker CX-100, 0.8 parts of mineral oil-based defoamer Foamaster MO 215, 2 parts of hydrophilic antifouling additive KP-912, and 12 parts of bio-based filler.

[0078] Example 3

[0079] The difference between Example 3 and Example 1 is that the degradable coating is made of the following raw materials in parts by weight: 80 parts of aqueous RPVB emulsion, 20 parts of aqueous polyurethane emulsion in Preparation Example 3, 4 parts of compatibilizer TPU (Desmopan TPU 60A), 0.8 parts of anti-UV additive-Tinuvin 1130, 0.8 parts of antioxidant 1010, 0.2 parts of antioxidant 168, 3 parts of dispersant, 1.2 parts of aqueous crosslinker Crosslinker CX-100, 0.8 parts of mineral oil-based defoamer Foamaster MO 215, 2 parts of hydrophilic antifouling additive KP-912, and 12 parts of bio-based filler.

[0080] Example 4

[0081] The difference between Example 4 and Example 1 is that the degradable coating is made of the following raw materials in parts by weight: 83.3 parts of aqueous RPVB emulsion, 16.7 parts of aqueous polyurethane emulsion in Preparation Example 1, 4 parts of compatibilizer TPU (Desmopan TPU 60A), 0.8 parts of anti-UV additive-Tinuvin 1130, 0.8 parts of antioxidant 1010, 0.2 parts of antioxidant 168, 3 parts of dispersant, 1.2 parts of aqueous crosslinker Crosslinker CX-100, 0.8 parts of mineral oil-based defoamer Foamaster MO215, 2 parts of hydrophilic antifouling additive KP-912, and 12 parts of bio-based filler.

[0082] Example 5

[0083] The difference between Example 5 and Example 1 is that the degradable coating is made of the following raw materials in parts by weight: 76.2 parts of aqueous RPVB emulsion, 23.8 parts of aqueous polyurethane emulsion in Preparation Example 1, 4 parts of compatibilizer TPU (Desmopan TPU 60A), 0.8 parts of anti-UV additive-Tinuvin 1130, 0.8 parts of antioxidant 1010, 0.2 parts of antioxidant 168, 3 parts of dispersant, 1.2 parts of aqueous crosslinker Crosslinker CX-100, 0.8 parts of mineral oil-based defoamer Foamaster MO215, 2 parts of hydrophilic antifouling additive KP-912, and 12 parts of bio-based filler.

[0084] Example 6

[0085] The difference between Example 6 and Example 1 is that the degradable coating is made of the following raw materials in parts by weight: 80 parts of aqueous RPVB emulsion, 20 parts of aqueous polyurethane emulsion in Preparation Example 1, 4 parts of compatibilizer TPU (Desmopan TPU 60A), 0.8 parts of anti-UV additive-Tinuvin 1130, 0.8 parts of antioxidant 1010, 0.2 parts of antioxidant 168, 3 parts of dispersant, 1.2 parts of aqueous crosslinker Crosslinker CX-100, 0.8 parts of mineral oil-based defoamer Foamaster MO 215, 2 parts of hydrophilic antifouling additive KP-912, and 30 parts of bio-based filler.

[0086] Example 7

[0087] The difference between Example 7 and Example 1 is that the degradable coating is made of the following raw materials in parts by weight: 80 parts of aqueous RPVB emulsion, 20 parts of aqueous polyurethane emulsion in Preparation Example 1, 4 parts of compatibilizer TPU (Desmopan TPU 60A), 0.8 parts of anti-UV additive-Tinuvin 1130, 0.8 parts of antioxidant 1010, 0.2 parts of antioxidant 168, 3 parts of dispersant, 1.2 parts of aqueous crosslinker Crosslinker CX-100, 0.8 parts of mineral oil-based defoamer Foamaster MO 215, 2 parts of hydrophilic antifouling additive KP-912, and 45 parts of bio-based filler.

[0088] Example 8

[0089] The difference between Example 8 and Example 1 is that the dispersant is a composite coupling agent combined with Dispex Ultra FA 4420, and the mass ratio of the composite coupling agent to Dispex Ultra FA 4420 is 8:2.

[0090] Example 9

[0091] The difference between Example 9 and Example 1 is that the dispersant is a composite coupling agent with Dispex Ultra FA 4420 and a titanate crosslinking agent TA-9-2, and the mass ratio of the composite coupling agent, Dispex Ultra FA 4420, and the titanate crosslinking agent TA-9-2 is 6:1:1.

[0092] Example 10

[0093] The difference between Example 10 and Example 1 is that the dispersant is composed of 2.36 parts of a composite coupling agent, 0.32 parts of DispexUltra FA4420, and 0.32 parts of a titanate crosslinking agent TA-9-2.

[0094] Embodiment 11

[0095] The difference between Example 11 and Example 1 is that the degradable coating is made of the following raw materials in parts by weight: 80 parts of aqueous RPVB emulsion, 20 parts of aqueous polyurethane emulsion in Preparation Example 1, 4 parts of compatibilizer TPU (Desmopan TPU 60A), 0.8 parts of anti-UV additive-Tinuvin 1130, 0.8 parts of antioxidant 1010, 0.2 parts of antioxidant 168, 3 parts of dispersant, 1.2 parts of aqueous crosslinker Crosslinker CX-100, 0.8 parts of mineral oil-based defoamer Foamaster MO 215, 2 parts of hydrophilic antifouling additive KP-912, and 30 parts of bio-based filler.

[0096] The bio-based filler is carbonized coconut shell fiber, carbonized coffee grounds powder, and coffee grounds-based activated carbon. The mass of the carbonized coconut shell fiber accounts for 5wt% of the total mass of the bio-based filler, the mass of the carbonized coffee grounds powder accounts for 20wt% of the total mass of the bio-based filler, and the remainder is coffee grounds-based activated carbon.

[0097] The length of the carbonized coconut shell fiber is 3-10 μm. The preparation method of the carbonized coconut shell fiber is to cut the dried coconut shell fiber into 3-10 μm pieces, then place the cut coconut shell fiber in a muffle furnace and heat it to 240° C. for 100 minutes, then heat it to 320° C. for 20 minutes, and cool the carbonized coconut shell fiber.

[0098] Carbonized coffee grounds powder is composed of nano carbonized coffee grounds powder with a particle size distribution of 0.1-0.3μm and submicron carbonized coffee grounds powder with a particle size distribution of 1-3μm. The mass ratio of nano carbonized coffee grounds powder with a particle size distribution of 0.1-0.3μm and submicron carbonized coffee grounds powder with a particle size distribution of 1-3μm is 6:4.

[0099] The average particle size of coffee grounds-based activated carbon is controlled at 3-6 μm.

[0100] The preparation method of coffee grounds-based activated carbon comprises the following steps: washing the ash and water-soluble substances on the surface of the coffee grounds with distilled water, and then placing the washed coffee grounds in an oven to dry; placing the dried coffee grounds in an externally heated vacuum pyrolysis device, heating the coffee grounds to 420°C at a rate of 20°C / min, with a vacuum degree of 0.02MPa, and degreasing the coffee grounds at a constant temperature for 60min to carbonize and degrease the coffee grounds to obtain a coffee grounds carbon precursor; placing the coffee grounds carbon precursor in a beaker, and adding an activator (phosphoric acid and distilled water) at an impregnation ratio (mass ratio of activator solute to coffee grounds precursor) of 2.0. The coffee grounds carbon precursor is soaked in a mixed solution of distilled water for 1 hour, ultrasonicated, and then dried; the dried raw materials are placed in an externally heated vacuum pyrolysis device, the heating rate is set to 20°C / min, the vacuum degree is 0.02MPa, and after the temperature is raised to the activation final temperature of 540°C, the coffee grounds carbon precursor is activated at a constant temperature for 80 minutes to obtain coffee grounds activated carbon, the obtained coffee grounds activated carbon is repeatedly washed with distilled water until it is neutral, dried after suction filtration, cooled, and fully ground and sieved to obtain coffee grounds-based activated carbon with an average particle size controlled at 3-6μm.

[0101] Example 12

[0102] The difference between Example 12 and Example 11 is that the mass of carbonized coconut shell fiber filaments accounts for 10wt% of the total mass of the bio-based filler, the mass of the carbonized coffee grounds powder accounts for 20wt% of the total mass of the bio-based filler, and the remainder is coffee grounds-based activated carbon.

[0103] Example 13

[0104] The difference between Example 13 and Example 11 is that the mass of carbonized coconut shell fiber filaments accounts for 20wt% of the total mass of the bio-based filler, the mass of the carbonized coffee grounds powder accounts for 20wt% of the total mass of the bio-based filler, and the remainder is coffee grounds-based activated carbon.

[0105] Embodiment 14

[0106] The difference between Example 14 and Example 11 is that the mass of carbonized coconut shell fiber filaments accounts for 30wt% of the total mass of the bio-based filler, the mass of carbonized coffee grounds powder accounts for 20wt% of the total mass of the bio-based filler, and the remainder is coffee grounds-based activated carbon.

[0107] Embodiment 15

[0108] The difference between Example 15 and Example 11 is that the mass of carbonized coconut shell fiber filaments accounts for 35wt% of the total mass of the bio-based filler, the mass of the carbonized coffee grounds powder accounts for 20wt% of the total mass of the bio-based filler, and the remainder is coffee grounds-based activated carbon.

[0109] Example 16

[0110] The difference between Example 16 and Example 11 is that the mass of carbonized coconut shell fiber filaments accounts for 20wt% of the total mass of bio-based filler, the mass of carbonized coffee grounds powder accounts for 20wt% of the total mass of bio-based filler, and the remainder is coffee grounds-based activated carbon. The carbonized coffee grounds powder is composed of nano-carbonized coffee grounds powder with a particle size distribution of 0.1-0.3μm and submicron carbonized coffee grounds powder with a particle size distribution of 1-3μm. The mass ratio of nano-carbonized coffee grounds powder with a particle size distribution of 0.1-0.3μm and submicron carbonized coffee grounds powder with a particle size distribution of 1-3μm is 8:2.

[0111] Embodiment 17

[0112] The difference between Example 17 and Example 11 is that the mass of carbonized coconut shell fiber filaments accounts for 20wt% of the total mass of bio-based filler, the mass of carbonized coffee grounds powder accounts for 20wt% of the total mass of bio-based filler, and the remainder is coffee grounds-based activated carbon. The carbonized coffee grounds powder is composed of nano-carbonized coffee grounds powder with a particle size distribution of 0.1-0.3μm and submicron carbonized coffee grounds powder with a particle size distribution of 1-3μm. The mass ratio of nano-carbonized coffee grounds powder with a particle size distribution of 0.1-0.3μm and submicron carbonized coffee grounds powder with a particle size distribution of 1-3μm is 3:1.

[0113] Embodiment 18

[0114] The difference between Example 18 and Example 11 is that the mass of carbonized coconut shell fiber filaments accounts for 20wt% of the total mass of bio-based filler, the mass of carbonized coffee grounds powder accounts for 20wt% of the total mass of bio-based filler, and the remainder is coffee grounds-based activated carbon. The carbonized coffee grounds powder is composed of nano-carbonized coffee grounds powder with a particle size distribution of 0.1-0.3μm and submicron carbonized coffee grounds powder with a particle size distribution of 1-3μm. The mass ratio of nano-carbonized coffee grounds powder with a particle size distribution of 0.1-0.3μm and submicron carbonized coffee grounds powder with a particle size distribution of 1-3μm is 9:1.

[0115] Embodiment 19

[0116] The difference between Example 19 and Example 11 is that the mass of carbonized coconut shell fiber filaments accounts for 20wt% of the total mass of bio-based filler, the mass of carbonized coffee grounds powder accounts for 20wt% of the total mass of bio-based filler, and the remainder is coffee grounds-based activated carbon. The carbonized coffee grounds powder is composed of nano-carbonized coffee grounds powder with a particle size distribution of 0.1-0.3μm and submicron carbonized coffee grounds powder with a particle size distribution of 1-3μm. The mass ratio of nano-carbonized coffee grounds powder with a particle size distribution of 0.1-0.3μm and submicron carbonized coffee grounds powder with a particle size distribution of 1-3μm is 1:1.

[0117] Embodiment 20

[0118] The difference between Example 20 and Example 11 is that the mass of carbonized coconut shell fiber filaments accounts for 20wt% of the total mass of the bio-based filler, the mass of carbonized coffee grounds powder accounts for 20wt% of the total mass of the bio-based filler, and the remainder is coffee grounds-based activated carbon. The carbonized coffee grounds powder is nano carbonized coffee grounds powder with a particle size distribution of 0.1-0.3μm.

[0119] Embodiment 21

[0120] The difference between Example 21 and Example 11 is that the mass of carbonized coconut shell fiber filaments accounts for 20wt% of the total mass of the bio-based filler, the mass of carbonized coffee grounds powder accounts for 20wt% of the total mass of the bio-based filler, and the remainder is coffee grounds-based activated carbon. The carbonized coffee grounds powder is composed of submicron carbonized coffee grounds powder with a particle size distribution of 1-3μm.

[0121] Embodiment 22

[0122] The difference between Example 22 and Example 11 is that the bio-based filler is carbonized coconut shell fiber and coffee grounds-based activated carbon. The mass of carbonized coconut shell fiber accounts for 20wt% of the total mass of the bio-based filler, and the remainder is coffee grounds-based activated carbon.

[0123] Comparative Example

[0124] The difference between Comparative Example 1 and Example 1 is that the degradable coating is made of the following raw materials in parts by weight: 100 parts of aqueous RPVB emulsion, 4 parts of compatibilizer TPU (Desmopan TPU 60A), 0.8 parts of anti-UV additive-Tinuvin 1130, 0.8 parts of antioxidant 1010, 0.2 parts of antioxidant 168, 3 parts of dispersant, 1.2 parts of aqueous crosslinker Crosslinker CX-100, 0.8 parts of mineral oil-based defoamer Foamaster MO 215, 2 parts of hydrophilic antifouling additive KP-912, and 12 parts of bio-based filler.

[0125] The difference between Comparative Example 2 and Example 1 is that the degradable coating is made of the following raw materials in parts by weight: 80 parts of aqueous RPVB emulsion, 20 parts of aqueous polyurethane emulsion in Preparation Example 4, 4 parts of compatibilizer TPU (Desmopan TPU 60A), 0.8 parts of anti-UV additive-Tinuvin 1130, 0.8 parts of antioxidant 1010, 0.2 parts of antioxidant 168, 3 parts of dispersant, 1.2 parts of aqueous crosslinker Crosslinker CX-100, 0.8 parts of mineral oil-based defoamer Foamaster MO215, 2 parts of hydrophilic antifouling additive KP-912, and 12 parts of bio-based filler.

[0126] The difference between Comparative Example 3 and Example 1 is that the degradable coating is made of the following raw materials in parts by weight: 90 parts of aqueous RPVB emulsion, 10 parts of aqueous polyurethane emulsion in Preparation Example 1, 4 parts of compatibilizer TPU (Desmopan TPU 60A), 0.8 parts of anti-UV additive-Tinuvin 1130, 0.8 parts of antioxidant 1010, 0.2 parts of antioxidant 168, 3 parts of dispersant, 1.2 parts of aqueous crosslinker Crosslinker CX-100, 0.8 parts of mineral oil-based defoamer Foamaster MO215, 2 parts of hydrophilic antifouling additive KP-912, and 12 parts of bio-based filler.

[0127] The difference between Comparative Example 4 and Example 1 is that the degradable coating is made of the following raw materials in parts by weight: 70 parts of aqueous RPVB emulsion, 30 parts of aqueous polyurethane emulsion in Preparation Example 1, 4 parts of compatibilizer TPU (Desmopan TPU 60A), 0.8 parts of anti-UV additive-Tinuvin 1130, 0.8 parts of antioxidant 1010, 0.2 parts of antioxidant 168, 3 parts of dispersant, 1.2 parts of aqueous crosslinker Crosslinker CX-100, 0.8 parts of mineral oil-based defoamer Foamaster MO215, 2 parts of hydrophilic antifouling additive KP-912, and 12 parts of bio-based filler.

[0128] The difference between Comparative Example 5 and Example 1 is that the degradable coating is made of the following raw materials in parts by weight: 80 parts of aqueous RPVB emulsion, 20 parts of aqueous polyurethane emulsion in Preparation Example 1, 4 parts of compatibilizer TPU (Desmopan TPU 60A), 0.8 parts of anti-UV additive-Tinuvin 1130, 0.8 parts of antioxidant 1010, 0.2 parts of antioxidant 168, 3 parts of dispersant, 1.2 parts of aqueous crosslinker Crosslinker CX-100, 0.8 parts of mineral oil-based defoamer Foamaster MO215, 2 parts of hydrophilic antifouling additive KP-912, and 5 parts of bio-based filler.

[0129] The difference between Comparative Example 6 and Example 1 is that the degradable coating is made of the following raw materials in parts by weight: 80 parts of aqueous RPVB emulsion, 20 parts of aqueous polyurethane emulsion in Preparation Example 1, 4 parts of compatibilizer TPU (Desmopan TPU 60A), 0.8 parts of anti-UV additive-Tinuvin 1130, 0.8 parts of antioxidant 1010, 0.2 parts of antioxidant 168, 3 parts of dispersant, 1.2 parts of aqueous crosslinker Crosslinker CX-100, 0.8 parts of mineral oil-based defoamer Foamaster MO215, 2 parts of hydrophilic antifouling additive KP-912, and 48 parts of bio-based filler.

[0130] The difference between Comparative Example 7 and Example 1 is that the degradable coating is made of the following raw materials in parts by weight: 80 parts of aqueous RPVB emulsion, 20 parts of aqueous polyurethane emulsion in Preparation Example 1, 4 parts of compatibilizer TPU (Desmopan TPU 60A), 0.8 parts of anti-ultraviolet additive-Tinuvin 1130, 0.8 parts of antioxidant 1010, 0.2 parts of antioxidant 168, 3 parts of dispersant, 1.2 parts of aqueous crosslinker Crosslinker CX-100, 0.8 parts of mineral oil-based defoamer Foamaster MO215, 2 parts of hydrophilic antifouling additive KP-912, and 12 parts of bio-based filler. The dispersant is a composite coupling agent.

[0131] The difference between Comparative Example 8 and Example 1 is that the degradable coating is made of the following raw materials in parts by weight: 80 parts of aqueous RPVB emulsion, 20 parts of aqueous polyurethane emulsion in Preparation Example 1, 4 parts of compatibilizer TPU (Desmopan TPU 60A), 0.8 parts of anti-ultraviolet additive-Tinuvin 1130, 0.8 parts of antioxidant 1010, 0.2 parts of antioxidant 168, 3 parts of dispersant, 1.2 parts of aqueous crosslinker Crosslinker CX-100, 0.8 parts of mineral oil-based defoamer Foamaster MO215, 2 parts of hydrophilic antifouling additive KP-912, and 12 parts of bio-based filler. The dispersant is KH550 coupling agent.

[0132] Performance testing

[0133] Detection method / test method

[0134] The control group was a degradable coating prepared with pure aqueous RPVB emulsion.

[0135] 1. The mechanical strength test of the degradable coating is carried out in accordance with the test method of GB / T 30776-2014_Adhesive tape tensile strength and elongation at break, and the testing equipment is WDW-2 electronic universal testing machine.

[0136] 2. Wear resistance test: Test the removable coating according to the GMW 3208-2012 rotary wear test. Observe whether the removable coating CS-10 1KG is damaged after 300 times. If CS-10 1KG is not damaged after 300 times, then CS-10 1KG is tested for 500 times to observe whether it is damaged. If CS-10 1KG is not damaged after 500 times, then CS-10 1KG is tested for 800 times to observe whether it is damaged.

[0137] 3. Tensile strength enhancement rate: The warp tensile strength of the base fabric was tested and recorded as F1. The warp tensile strength of the composite fabrics of Examples 1-22 and Comparative Examples 1-8 after the composite degradable coating was tested and recorded as F2. Tensile strength enhancement rate △T (%) = (F2-F1)*100 / F1.

[0138] Data analysis

[0139] Table 1 shows the test parameters of Examples 1-22 and Comparative Examples 1-8

[0140]

[0141]

[0142] Combining Examples 1-22 and Comparative Examples 1-8 and Table 1, it can be seen that compared with Comparative Example 1-2, the mechanical properties and wear resistance of Example 1-3 are better than those of Comparative Example 2, and the mechanical properties and wear resistance of Example 1-3 are close to those of Comparative Example 1, but Example 1-3 has a certain puncture self-healing effect. Therefore, the composite emulsion formed by the aqueous RPVB emulsion and the aqueous polyurethane emulsion as the matrix overcomes the defect of mechanical strength deviation caused by the poor compatibility of the bio-based filler and the matrix resin in the prior art, and gives the degradable coating composite fabric better mechanical properties and better green environmental protection performance.

[0143] Combining Examples 1-22 and Comparative Examples 1-8 and Table 1, it can be seen that the mechanical strength of Examples 1-5 is better than that of Comparative Examples 2-3 and is close to that of Comparative Examples 1 and 4. Therefore, considering the comprehensive cost and physical and chemical properties, the mass ratio of the aqueous RPVB emulsion and the aqueous polyurethane emulsion in the degradable coating is controlled at (80-100): (20-25), which is more suitable. The combination of aqueous polyurethane emulsion and bio-based filler can improve the overall wear resistance.

[0144] Combining Examples 1-22 and Comparative Examples 1-8 with Table 1, it can be seen that compared with the control group and Comparative Examples 5-6, Examples 1 and 6-7 have better comprehensive performance than the control group and Comparative Examples 5 and 6. Therefore, considering the comprehensive cost and physical and chemical properties, the amount of bio-based filler added in the degradable coating is preferably controlled at 12-45 parts of bio-based filler, and the preferred amount is 30-32 parts.

[0145] Combining Examples 1-22 and Comparative Examples 1-8 and Table 1, it can be seen that compared with Comparative Examples 7-8, Examples 1 and Examples 8-10 have better mechanical properties than Comparative Examples 7-8. Therefore, the use of the dispersant in the present application can make the bio-based filler dispersed in the composite emulsion formed by the aqueous RPVB emulsion and the aqueous polyurethane emulsion. The bio-based filler has good compatibility with the composite emulsion, and the formed degradable coating has good mechanical properties and mechanical strength enhancement effect.

[0146] Combining Examples 1-22 and Comparative Examples 1-8 and Table 1, it can be seen that the mechanical properties of Examples 1 and Examples 8-10 are slightly better than those of Example 8. Therefore, the dispersant is a composite coupling agent with Dispex Ultra FA 4420 and a titanate crosslinker TA-9-2, and the mass ratio of the composite coupling agent, Dispex Ultra FA 4420, and the titanate crosslinker TA-9-2 is (6-8): 1:1. The degradable coating formed has good mechanical properties and mechanical strength enhancement effect.

[0147] Combining Examples 1-22 and Comparative Examples 1-8 and Table 1, it can be seen that compared with Examples 11-15, the comprehensive mechanical properties of Examples 11-15 are better than those of Example 6. Although the tensile fracture rate of Examples 11-15 is slightly reduced, the decline is small and the impact on the overall mechanical properties is also small. Therefore, the degradable coating prepared by carbonizing coconut shell fiber filaments, carbonizing coffee grounds powder, and coffee grounds-based activated carbon has better mechanical strength and mechanical enhancement performance. The comprehensive mechanical properties of Examples 12-13 are better than those of Examples 11 and 15. Therefore, the mass of carbonized coconut shell fiber filaments accounts for 10-30wt% of the total mass of the bio-based filler, the mass of the carbonized coffee grounds powder accounts for 20-50wt% of the total mass of the bio-based filler, and the remainder is coffee grounds-based activated carbon. The prepared degradable coating has good mechanical properties and mechanical strength enhancement effect.

[0148] In combination with Examples 1-22 and Comparative Examples 1-8 and in combination with Table 1, it can be seen that by comparison between Example 13 and Examples 16-22, the mass ratio of nano-carbonized coffee grounds powder with a particle size distribution of 0.1-0.3 μm and submicron carbonized coffee grounds powder with a particle size distribution of 1-3 is (6-8): (2-4), the production cost is relatively low and the prepared degradable coating has good mechanical properties and mechanical strength enhancement effect.

[0149] To sum up, in this application, the base fabric is subjected to low-temperature plasma treatment and the degradable coating adopts a composite emulsion formed by water-based RPVB emulsion and water-based polyurethane emulsion, so that the base fabric and the degradable coating have good peel strength. Therefore, this application not only has good degradability and good environmental performance, which is in line with the development trend of low-carbon and environmental protection, but also has relatively good mechanical properties, wear resistance, and stability in use, which can improve the overall quality of the fabric and expand its application range.

[0150] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A degradable coating composite fabric prepared using biological residues, comprising a base fabric, characterized in that: The surface of the base fabric is compounded with a degradable coating; the degradable coating is mainly prepared from the following raw materials in parts by weight: 80-100 parts of water-based RPVB emulsion, 20-25 parts of water-based polyurethane emulsion, 3-8 parts of compatibilizer, 0.5-2 parts of anti-ultraviolet additive, 0.5-2 parts of antioxidant, 1-5 parts of dispersant, 12-45 parts of bio-based filler; the solid content of the water-based RPVB emulsion is 40-55%, and the solid content of the water-based polyurethane emulsion is 30-45%; the average particle size of the bio-based filler is controlled at 0.1-10μm; the bio-based filler is carbonized coconut shell fiber, carbonized coffee grounds powder, coffee grounds-based activated carbon; the carbonized coconut shell The length of the fiber filaments is 3-10 μm; the carbonized coffee grounds powder is composed of nano carbonized coffee grounds powder with a particle size distribution of 0.1-0.3 μm and submicron carbonized coffee grounds powder with a particle size distribution of 1-3 μm; the mass ratio of the nano carbonized coffee grounds powder with a particle size distribution of 0.1-0.3 μm and the submicron carbonized coffee grounds powder with a particle size distribution of 1-3 μm is (6-8): (2-4); the average particle size of the coffee grounds-based activated carbon is controlled at 3-6 μm; the mass of the carbonized coconut shell fiber filaments accounts for 10-30wt% of the total mass of the bio-based filler, the mass of the carbonized coffee grounds powder accounts for 20-50wt% of the total mass of the bio-based filler, and the remainder is coffee grounds-based activated carbon.

2. The degradable coating composite fabric prepared by using biological residues according to claim 1, characterized in that: The degradable coating is mainly prepared from the following raw materials in parts by weight: 100 parts of water-based RPVB emulsion, 20-25 parts of water-based polyurethane emulsion, 4-6 parts of compatibilizer, 0.8-1.2 parts of anti-ultraviolet additive, 1-1.5 parts of antioxidant, 3-4 parts of dispersant, 25-35 parts of bio-based filler, 0.5-2 parts of water-based crosslinking agent, 0.5-2 parts of mineral oil-based defoaming agent, 1-3 parts of hydrophilic antifouling agent; the water-based crosslinking agent is one of Neoadd PAX-524 water-based crosslinking agent and Crosslinker CX-100 water-based crosslinking agent; the mineral oil-based defoaming agent is one of Foamaster MO 2150 and Foamaster MO NXZ; the hydrophilic antifouling agent is one of KP-912, KP-913 and KP-914.

3. The degradable coating composite fabric prepared by using biological residues according to claim 1 or 2, characterized in that: The aqueous polyurethane emulsion is prepared from the following raw materials: isocyanate, polyol, catalyst, chain extender, dimethylglyoxime, triethanolamine, acetone and deionized water; the chain extender is 1,6-hexanediol and ethylenediamine; the molar ratio of 1,6-hexanediol to ethylenediamine is 1:(0.5-2); the polyol is polycarbonate polyol and polytetrahydrofuran polyol with a weight average molecular weight of 2000-3000; the molar ratio of the polycarbonate polyol to the polytetrahydrofuran polyol is (8-9):(1-2); the molar ratio of the active groups in the dimethylglyoxime is 0.2-0.4 times the total molar amount of the active groups in the polyol and the chain extender; the molar ratio of the polyol to the chain extender is 1:(2.5-2.8).

4. The degradable coating composite fabric prepared by using biological residues according to claim 3 is characterized by: The preparation method of the waterborne polyurethane emulsion comprises the following steps: firstly weighing polyol, isocyanate and catalyst according to a formula, mixing them evenly, heating to 85-95°C, reacting for 2-2.5h, adding a chain extender, reacting at 70-80°C for 40min, adding dimethylglyoxime, and continuing to react for 1-1.5h; then adding acetone to dilute, cooling to 40-45°C, adding triethanolamine to neutralize, adding deionized water to disperse evenly at high speed, and removing acetone by distillation to obtain the target waterborne polyurethane emulsion.

5. The degradable coating composite fabric prepared by using biological residues according to claim 1, characterized in that: The dispersant is a composite coupling agent combined with one of Dispex Ultra FA 4416, 4420, and 4430; the preparation method of the composite coupling agent comprises mixing N-phenylaminomethyl triethoxysilane and 3-methacryloxypropyl triethoxysilane in a molar ratio of 1: (1.02-1.08) evenly, and then refluxing at 80-95° C. for 3-6 hours to obtain the composite coupling agent.

6. The degradable coating composite fabric prepared by using biological residues according to claim 4, characterized in that: The dispersant is a composite coupling agent, Dispex Ultra FA 4420, and a titanate crosslinking agent TA-9-2; the mass ratio of the composite coupling agent, Dispex Ultra FA 4420, and the titanate crosslinking agent TA-9-2 is (6-8): 1:

1.

7. The degradable coating composite fabric prepared by using biological residues according to claim 1, characterized in that: The antioxidant is one or more combinations of antioxidant 1010, antioxidant 168, antioxidant 1076, and antioxidant 1024; the anti-ultraviolet additive is one or more combinations of UV-326, UV-292, UV-77DF, Tinuvin 1130, Tinuvin 5151, and Tinuvin5333-DW (N); and the compatibilizer is one or more combinations of POP grafted maleic anhydride, TPO, TPV, TPU, and TPEE.

Citation Information

Patent Citations

  • Water-based surface polyurethane resin for automobile leather and preparation method of water-based surface polyurethane resin

    CN112341593A

  • Film-like material with tactile structure and manufacturing method of film-like material

    CN113402752A